PENDAMPINGAN PENYUSUNAN RENCANA PEMBANGUNAN JANGKA MENENGAH (RPJM) NAGARI PAKAN SINAYAN: Assistance in the Preparation of the Nagari Pakan Sinayan Medium Term Development Plan (RPJM) - Yulia Ningsih; Rina Mulyani; Nova Marlianti; Niko Armonisaputra (ASOSIASI IDEBAHASA KEPRI, 2023)
The community service aims to increase the understanding of stakeholders, especially Nagari officials, members of the Board of Commissioners, members of institutions, and community representatives in Nagari Pakan Sinayan regarding the ways to prepare the Nagari RPJM document so as to produce a draft document for Nagari Pakan Sinayan's Medium Term Development Plan and this activity gave rise to the draft Nagari development plan in accordance with the regulations of the Minister of Home Affairs (Kemendagri) Numbers 37 and 66 in 2007. The methods used in this activity are lectures, questions and answers, discussions, and assistance in preparing the RPJM Nagari. Implementation of preparation assistance in the form of providing material for 1 day and technical assistance activities for 2 months to provide guidance and assistance in perfecting the drafting of the Nagari RPJM document which is adjusted to the Regional RPJM, Regency Strategic Plan, and the Vision and Mission of the elected Walinagari.